Implementasi Sistem Pengendalian Internal dalam Upaya Mewujudkan Good Governance pada Lembaga Layanan Pendidikan Tinggi - Maharani, Riantari; BZ, Fazli Syam; Priantana, Riha Dedi (Fakultas Ekonomi Universitas Samudra, 2023)
The study aims to test the effect of the performance of the internal supervision unit, organizational culture, and organizational commitment toward the internal control system implementation for the implementation of good governance at the higher education service institution. Data analysis techniques using path analysis using data obtained from the distribution of questionnaires in 150 respondents. The results showed that the implementation of the internal control system in an effort to realize good governance was influenced by the performance of the internal supervision unit, organizational culture, and organizational commitment. The performance of the internal supervision unit has a very high influence on the implementation of the internal control system so that it is able to realize good governance in Higher Education Service Institutions.